2021
DOI: 10.3171/2021.2.peds20983
|View full text |Cite
|
Sign up to set email alerts
|

Spring-mediated cranioplasty versus endoscopic strip craniectomy for sagittal craniosynostosis

Abstract: OBJECTIVE Endoscopic strip craniectomy (ESC) and spring-mediated cranioplasty (SMC) are two minimally invasive techniques for treating sagittal craniosynostosis in early infancy. Data comparing the perioperative outcomes of these two techniques are sparse. Here, the authors hypothesized that outcomes would be similar between patients undergoing SMC and those undergoing ESC and conducted a study using the multicenter Pediatric Craniofacial Surgery Perioperative Registry (PCSPR). METHODS The PCSPR was queried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Multiple factors must be considered when weighing early intervention with strip craniectomy and spring-mediated cranioplasty or molding orthosis versus whole-vault cranioplasty for children with sagittal craniosynostosis. 36–40 This study using OCT technology concluded that elevated ICP appears to be very uncommon when minimally invasive surgical correction is undertaken earlier than 6 months of age, whereas children older than 6 months have a significantly higher likelihood of elevated ICP. We believe that this adds to the potential advantages of earlier intervention in patients who present in the first 6 months of life, acknowledging the importance of further research to clarify the relationship between ICP and neurocognitive outcomes.…”
Section: Discussionmentioning
confidence: 98%
“…Multiple factors must be considered when weighing early intervention with strip craniectomy and spring-mediated cranioplasty or molding orthosis versus whole-vault cranioplasty for children with sagittal craniosynostosis. 36–40 This study using OCT technology concluded that elevated ICP appears to be very uncommon when minimally invasive surgical correction is undertaken earlier than 6 months of age, whereas children older than 6 months have a significantly higher likelihood of elevated ICP. We believe that this adds to the potential advantages of earlier intervention in patients who present in the first 6 months of life, acknowledging the importance of further research to clarify the relationship between ICP and neurocognitive outcomes.…”
Section: Discussionmentioning
confidence: 98%
“…8 Although the election for endoscopic versus open procedures is certainly a multifaceted one, emerging literature highlights the favorable peri- and postoperative profile of endoscopic approaches for several craniofacial operations, including reduced blood loss, 13 decreased operative time, 13 and shorter ICU length of stay. 14,15 Additionally, academic institutions often have multiple clinicians in any given specialty from which knowledge bases can be tapped to maximize patient care. It is unreasonable to expect a team's craniofacial surgeon to suggest robust solutions to a patient's otologic concerns compared to those offered by the team's pediatric otolaryngologist, and vice versa.…”
Section: Centersmentioning
confidence: 99%